ICT in telemedicine: conquering privacy and security issues in health care services - Olanrewaju, Rashidah Funke; Ali , Nor'ashikin; Khalifa, Othman Omran; Abdul Manaf, Azizah (2012)
Advancement in telecommunication combined with improved information technology infrastructures has opened up new dimensions in e-health environment. Such technologies make readily available to access, store, manipulate and replicate medical information and images. These technologies help reduced the time and effort in diagnoses and treatment at lower cost. However, protection and authentication of such medical information and images are now becoming increasingly important in telemedicine environment, where images are readily distributed over electronic networks. Intruders/hackers may gain access to confidential information and possible alter or even delete such vital records. The ultimate success of telemedicine demands an effective technology as well as privacy and security of records should be main concern. This paper explores recent identified privacy and security issues that affect telemedicine. Featuring threats on security and authentication of medical records, and proposing digital watermarking as a technology to curb authentication issues in telemedicine is highlighted.